2015
DOI: 10.1152/ajpregu.00012.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular control in women with fibromyalgia syndrome: do causal methods provide nonredundant information compared with more traditional approaches?

Abstract: -The cardiovascular autonomic control and the baroreflex sensitivity (BRS) have been widely studied in fibromyalgia syndrome (FMS) patients through the computation of linear indices of spontaneous heart period (HP) and systolic arterial pressure (SAP) variabilities. However, there are many methodological difficulties regarding the quantification of BRS by the traditional indices especially in relation to the issue of causality. This difficulty has been directly tackled via a model-based approach describing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…Our finding that cBRS decreased with active and passive standing postures compared to the lying position (Table 1, Figure 4C) agrees with previous work (Steptoe and Vögele, 1990; O'Leary et al, 2003; Nollo et al, 2005; Faes et al, 2013; Schwartz et al, 2013; Zamunér et al, 2015). Moreover, our finding that cBRS in the supine position significantly decreased after the loss of more than 0.33 L of blood is in line with previous reports (Hughson et al, 1994; Saitoh et al, 2008) obtained using lower-body negative pressure, which also decreases CVP in the supine position.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that cBRS decreased with active and passive standing postures compared to the lying position (Table 1, Figure 4C) agrees with previous work (Steptoe and Vögele, 1990; O'Leary et al, 2003; Nollo et al, 2005; Faes et al, 2013; Schwartz et al, 2013; Zamunér et al, 2015). Moreover, our finding that cBRS in the supine position significantly decreased after the loss of more than 0.33 L of blood is in line with previous reports (Hughson et al, 1994; Saitoh et al, 2008) obtained using lower-body negative pressure, which also decreases CVP in the supine position.…”
Section: Discussionsupporting
confidence: 91%
“…A set of analysis techniques based on information theory (Nollo et al, 2005; Porta et al, 2011, 2014, 2015; Faes et al, 2013; Zamunér et al, 2015) has been applied to infer the direction and strength of causal links between the time series of SAP and HP. A rather straightforward interpretation of causality is afforded by these techniques at the expense of significant computational and theoretical complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, autonomic function and cardiovascular control have been frequently assessed in FMS and their evaluation has been typically based on the analysis of spontaneous fluctuations of heart period (HP) and systolic arterial pressure (SAP) [26]. These studies have reported that patients with FMS feature an increased sympathetic control and a reduced vagal modulation in supine position at rest (REST) [4,7,8], a lower cardiac baroreflex sensitivity compared to age-matched healthy subjects at REST [4,7,8], an inability of reducing further baroreflex sensitivity during an orthostatic challenge such as active standing (STAND) [6] and a limited involvement of the baroreflex control in regulating arterial blood pressure during STAND as detected by Granger causality analysis [6]. However, whether all these parameters derived from HP and SAP variabilities are related to the quality of life of the FMS patient, as assessed from a clinical score such as the fibromyalgia impact questionnaire (FIQ) and the visual analog score for pain (VAS pain), is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recent studies have used the active standing test to assess the cardiovascular autonomic control responses to the orthostatic stimulus in several disorders, including FMS. 4 However, there are few studies correlating symptoms and clinical factors with cardiovascular autonomic dysfunction. Objectives: To assess the relationship between the impact of fibromyalgia on quality of life and cardiac autonomic control response to the active standing test.…”
Section: St Vincents University Hospital Dublin Irelandmentioning
confidence: 99%